Diagnosing delirium in older hospitalized adults with dementia: adapting the confusion assessment method to international classification of diseases, tenth revision, diagnostic criteria - Thomas, Christine; Oster, Peter (Journal of the American Geriatrics Society, 2012)
Objectives: To compare performance characteristics of the Confusion Assessment Method (CAM) algorithm for screening and delirium diagnosis with criteria for delirium from the International Classification of Diseases, Tenth Revision (ICD-10) and Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV) in high-risk individuals. Design: Prospective cohort study. Setting: Academic geriatric hospital. Participants: One hundred two individuals aged 80 to 100 hospitalized for acute medical illness. Measurements: Complete CAM instrument (nine items), scored using the four-item CAM diagnostic algorithm. Criterion standard classification of delirium was rated independently according to expert consensus based on DSM-IV and ICD-10 criteria for delirium. Results: In 79 hospitalized participants, the CAM performed well for delirium screening (delirium prevalence of 24% according to DSM-IV and 14% according to ICD-10). Of all CAM features, acute onset and fluctuating course are most important for diagnosis (area under the receiver operating characteristic curve (AUC) = 0.92 in DSM-IV and 0.83 in ICD-10). The CAM diagnostic algorithm had a sensitivity of 0.74, a specificity of 1.0, and an AUC of 0.88 compared with the DSM-IV reference standard and a sensitivity of 0.82, a specificity of 0.91, and an AUC of 0.85 compared with the ICD-10. Compared with the ICD-10, adding psychomotor change to the CAM algorithm improved specificity to 97%, but sensitivity fell to 55% (AUC = 0.96). Applying psychomotor change sequentially only to the group that the CAM algorithm identified as having no delirium improved sensitivity to 91% with specificity of 85% (AUC = 0.95). Conclusion: Although the CAM diagnostic algorithm performed well against a DSM-IV reference standard, adding psychomotor change to the CAM algorithm improved specificity and diagnostic value against ICD-10 criteria overall in older adults with dementia and improved sensitivity and screening performance when applied sequentially in CAM-negative individuals.